2018
DOI: 10.1177/0093854818810314
|View full text |Cite
|
Sign up to set email alerts
|

Hate Crimes Hurt More, but so Do Co-Offenders: Separating the Influence of Co-Offending and Bias on Hate-Motivated Physical Injury

Abstract: One of the primary motivations for hate crime laws is that hate crimes “hurt more.” But hate crimes are often committed by groups, and research indicates that crimes committed by groups are also more violent than other crimes. This research focuses on one type of harm, physical injury, asking, are hate crimes more violent because they involve co-offenders or because of the bias motivation behind the incident? Results using data from the National Incident-Based Reporting System (NIBRS) indicate that hate crimes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
33
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 46 publications
(38 citation statements)
references
References 56 publications
0
33
0
1
Order By: Relevance
“…First, although useful, an examination of heterogeneity in arrest risk for all offenses in the NIBRS data would be beyond the scope of a single analysis. Because recent research has suggested that co-offending may be especially consequential in the production of violence (e.g., Lantz, 2018; Lantz & Kim, 2018; McGloin & Piquero, 2009), this research focuses on violent offenses as a starting point. Second, because the victim does not necessarily encounter the offender during property crimes, information regarding offender demographics—one of the primary foci of this research—are considerably more reliable for violent crimes.…”
Section: Methodsmentioning
confidence: 99%
“…First, although useful, an examination of heterogeneity in arrest risk for all offenses in the NIBRS data would be beyond the scope of a single analysis. Because recent research has suggested that co-offending may be especially consequential in the production of violence (e.g., Lantz, 2018; Lantz & Kim, 2018; McGloin & Piquero, 2009), this research focuses on violent offenses as a starting point. Second, because the victim does not necessarily encounter the offender during property crimes, information regarding offender demographics—one of the primary foci of this research—are considerably more reliable for violent crimes.…”
Section: Methodsmentioning
confidence: 99%
“…Recent research on co-offending as collective behavior argues that the presence of co-offenders allows individuals to engage in behavior that they would never have engaged in had they been alone (Lantz, 2018; Lantz & Kim, 2019; McGloin & Piquero, 2009; Warr, 2002). More specifically, this research argues that being in the presence of other offenders changes the threshold for certain behaviors through various mechanisms, including the diffusion of responsibility among group members (Granovetter, 1978; McGloin & Rowan, 2015).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Using descriptive data in Canada, Carrington (2002) found that groups were more likely than solo offenders to commit more serious crimes, and that a higher percentage of crimes resulting in injury involved co-offenders, rather than a single offender. More recently, Lantz (2018) examined injury likelihood in a multivariate framework and found that incidents committed by groups were more likely to involve serious injury, and that the likelihood of serious injury increased as the size of a co-offending group increased (see also Lantz & Kim, 2019).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Prior research has consistently demonstrated hate crimes to be quantitatively and qualitatively more severe (i.e., violent) than other types of nonbias crimes (Harlow, 2005;Lantz & Kim, 2019;B. Levin, 1999;J.…”
Section: Literature Reviewmentioning
confidence: 99%
“…toward the characteristics of the victim (i.e., race, religion, sex, sexual orientation, disability, etc. ), are more severe than other crimes; in other words, hate crimes "hurt more" (Iganski, 2001;Lantz & Kim, 2019). In general, scholars have pointed to three ways in which hate crimes hurt more than other crimes.…”
mentioning
confidence: 99%